A Framework for Enhancing Higher Education in The Kurdistan Region of Iraq through A Dedicated Digital Education Mooc - Abdulazeez, Dezheen (2021)
Technology-enhanced learning is utilized to support teaching and learning processes by using technology. ICT has enabled Open Online Learning to become a phenomenon and a prominent feature of higher education in developed countries because it can deliver a wide range of high-quality courses to a massive number of students and increase the collaborative learning experience among learners. It is possible to suggest that the range of pedagogical practices based on open online learning. MOOCs are presently shifting the educational landscape from classical scenarios to digital scenarios where open educational resources are being shared among universities and institutions. In this paper, a framework based on open online learning for serving higher education institutions in the Kurdistan Region of Iraq is proposed. The proposed framework aims to serve teachers and students by providing adapted high-quality contents and scaffolding teaching and learning processes, in a cultural-aware context, in order to improve the existing higher education system.